2016
DOI: 10.1063/1.4952389
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal annealing on the spin injection and spin detection through Fe/GaAs interfaces

Abstract: A strong bias asymmetry of the spin-injection efficiency through an epitaxial Fe/GaAs Schottky tunnel contact is observed. Low-temperature post-growth thermal annealing is shown to strongly affect the spin-injection efficiency. The annealing leads either to a reduction or an enhancement. The spin accumulation is addressed electrically in a lateral spin-valve geometry using a non-local spin-valve setup at liquid helium temperatures. A spin-injection efficiency of up to 5.5% is estimated from experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…1 For ferromagnetic bcc Fe, GaAs is a suitable substrate to achieve epitaxy because of the small lattice-misfit (1.4%). The research on epitaxial Fe/GaAs structures is of ongoing interest for injection and detection of spin polarized electrons, [2][3][4] and the study of magnetism in reduced dimensions and at interfaces. 5,6 For a long time, molecular beam epitaxy (MBE), was the preferred method for the fabrication of Fe/GaAs structures.…”
mentioning
confidence: 99%
“…1 For ferromagnetic bcc Fe, GaAs is a suitable substrate to achieve epitaxy because of the small lattice-misfit (1.4%). The research on epitaxial Fe/GaAs structures is of ongoing interest for injection and detection of spin polarized electrons, [2][3][4] and the study of magnetism in reduced dimensions and at interfaces. 5,6 For a long time, molecular beam epitaxy (MBE), was the preferred method for the fabrication of Fe/GaAs structures.…”
mentioning
confidence: 99%
“…6 Other reports also indicate a strong influence of post-growth annealing on spin injection efficiency. [7][8][9] We also observed a similar effect, 10 where the non-local spin signal was observed only after a soft post-annealing of the structures to 200 C. To date, several studies were attempted to correlate post growth annealing and spin injection by analyzing the atomic structure of the FM/SC interface. Zega et al proposed a model of ordered and coherently intermixed interface of Fe and As atoms.…”
Section: Introductionmentioning
confidence: 55%
“…Both the metal layers were deposited at room temperature. The sample layout designed for spin transport experiments 10 with nominal thicknesses is shown in Fig. 1.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…In fact, for Si, it is shown that a very thin (70 nm) channel thickness led to a higher spin accumulation possibly due to the confinement of injected spins [25]. To eliminate further spurious sources of the field-dependent signals, nonmagnetic metals could be used as the source and the drain contacts for the non-local injection and detection [26]. As the key step to test the feasibility of the optical gating of the non-local spin transport, the circularly-polarised light at the 822 nm wavelength was illuminated to the region of pure spin current between the injector and the detector ferromagnets as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%